Quantum Mechanical/Molecular Mechanical (QM/MM) Car-Parrinello Simulations in Excited States - Marc-Etienne Moret; Enrico Tapavicza; Leonardo Guidoni; Ute F. Röhrig; Marialore Sulpizi; Ivano Tavernelli; Ursula Rothlisberger (CHIMIA, 2005)
The combination of time-dependent density functional theory (TDDFT) for the description of excited states with a hybrid quantum mechanics/molecular mechanics (QM/MM) approach enables the study of photochemical processes in complex environments. Here, we present a short overview of recent applications of TDDFT/MM approaches to a variety of systems including studies of the optical properties of prototypical organic and inorganic molecules in gas phase and solution, photoinduced electron transfer reactions in donor-bridge-acceptor complexes, and in situ investigations of the molecular mechanisms of photoactive proteins. The application of TDDFT/MM techniques to a wide range of systems enables an assessment of the current performance and limitations of these methods for the characterization of photochemical processes in complex systems.